Influence of thickness of transverse and longitudinal layers on deformability and stress distribution in five-layer cross-glued wood boards - M. Yu. Troshin; A. V. Turkov (Vestnik MGSU)
Introduction. A distinctive feature of CLT panels is the cross arrangement of planks (lamellae) in different layers of the board. Due to the anisotropy of wood, this design allows for high strength and stiffness in different directions of stress action, which has made this material one of the most promising to be studied in recent decades. This article examines the influence of the thickness of transverse and longitudinal layers in five-layer slabs of cross-glued timber boards, or CLT panels, on the deformation and distribution of the resulting normal and tangential stresses. The relevance of the work is conditioned by the necessity of obtaining calculated data to analyze changes in the strength characteristics of boards with different variations in the thickness of longitudinal and transverse layers in order to choose the most effective configuration of the board.Materials and methods. The studies were carried out by numerical methods using SCAD+ PC using FEM (Finite element method). At the same time, the three-dimensional finite elements are parallelepipeds. The design scheme is defined as a general-type system, whose deformations and its main unknowns are represented by linear displacements of nodal points along the X, Y, Z axes and rotations around these axes. As a design structure, a five-layer slab with cross-directed layers was chosen in such a way that the outer (1, 5) and central inner (3) layers are longitudinal, and the remaining inner (2, 4) are transverse. The simplified design scheme is a pivotally supported beam.Results. The results of the study and calculations made using SCAD+ were applied to make tables and graphs showing dependence of deflection, distribution of normal and tangential stresses on the thickness of transverse and longitudinal layers of the board.Conclusions. The obtained data allow us to evaluate the influence of thickness on deformability and stress distribution in five-layer CLT panels. The significance of the conducted research is in the expansion of scientific and technical knowledge base in the field of wooden structures.